Media PowerPoint dalam Pembelajaran - Muthoharoh, Miftakhul (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2019)
Media is a learning tool that every teacher needs to pay attention to when they want to carry out the teaching and learning process because if there is no development in the use of media in learning, the teaching and learning process will be monotonous and unpleasant, even students tend to be lazy to take part in learning. if this happens it is certain that the failure of the teaching and learning process has failed. Facing the digital era 4.0, a teacher must be really able to use various kinds of multimedia in learning, teachers are not allowed to only use student worksheets when teaching. In this era, teachers should use technology-based learning media such as the internet or use Microsoft PowerPoint as a medium when they want to deliver material to students.